Волки Лозарга: роман : в 2 кн. : пер. с фр. (Ж. Бенцони) - Бенцони Жюльетта (Волки Лозарга, 2010)
Экземпляры: ф4 (20180506) / Инвентарный номер: 193373 / Цена: / Сис.шифр: 84(4/8) / Авт.знак: Б 46 / ГРНТИ: 17.82 / ББК: 84(4Фра)